Surface and interface engineering in transition metal–based catalysts for electrochemical water oxidation - Singh B.; Indra A. (My University, 2025)
A tremendous effort has been provided in last two decades to develop efficient transition metal–based heterogeneous catalysts for the electrochemical water oxidation. Several approaches such as composition modulation, heteroatom doping, morphological development, particle size tuning, surface area enhancement, and control over electronic structure have been explored for the designing of the materials with improved water oxidation activity. As the electrochemical process is a surface phenomenon, surface structure plays a crucial role in controlling the water oxidation activity. Rational engineering of the catalyst surface by composition modulation, crystal facet tuning, and generating functional overlayer has been reported to enhance the water oxidation activity. Heteroatom doping, cationic and anionic deficiencies, and ultrathin 2D morphology are also found to promote electrochemical performance. In addition, engineering in the interface provides intrinsic improvement of the catalytic activity and stability for the electrochemical water oxidation. Although, surface and interface engineering of the catalyst has come out as the major factors in the electrochemical water oxidation, no dedicated review is available in this field. In this review, we have described the strategies of improving water oxidation activity of the catalysts by surface and interface engineering. The progress in this field discussed in detail; the challenges have been identified and addressed to attain a clear understanding in this field. © 2020 Elsevier Ltd